EVALUATING QUALITY OF EXPERIENCE (QoE) AND BROADBAND ADOPTION IN PUBLIC HIGHER EDUCATIONAL INSTITUTIONS: INSIGHTS FOR IMPROVED SERVICE QUALITY AND ACCESS - Suheil Che Sobry; Muhammad Zarunnaim Haji Wahab; Mohd Hilal Muhammad; Muhammad Saiful Islam Ismail; Ahmad Harith Ashrofie Hanafi; Norhasyikin Rozali, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This study investigates the relationship between the Quality of Experience (QoE) dimensions and broadband service adoption among students in Public Higher Educational Institutions (PHEIs). Four key QoE dimensions; service coverage, service quality, service reliability, and service usability are examined for their impact on broadband adoption rates. A survey of 217 students from public universities was conducted to assess these relationships. Results indicate that service usability and service coverage significantly influence broadband adoption, while service reliability and service quality show positive correlations with broadband adoption. The findings provide insights into improving broadband service strategies in PHEIs, highlighting the importance of ensuring robust, high-quality, and user-friendly services to increase broadband adoption. This study contributes to the understanding of QoE in the context of educational institutions and offers actionable recommendations for policymakers and service providers aiming to enhance service quality and access to broadband networks.